Dual-Energy CT of the Heart: A Review - Serena Dell’Aversana; Raffaele Ascione; Marco De Giorgi; Davide Raffaele De Lucia; Renato Cuocolo; Marco Boccalatte; Gerolamo Sibilio; Giovanni Napolitano; Giuseppe Muscogiuri; Sandro Sironi; Giuseppe Di Costanzo; Enrico Cavaglià; et al. (Journal of Imaging, 2022)
Dual-energy computed tomography (DECT) represents an emerging imaging technique which consists of the acquisition of two separate datasets utilizing two different X-ray spectra energies. Several cardiac DECT applications have been assessed, such as virtual monoenergetic images, virtual non-contrast reconstructions, and iodine myocardial perfusion maps, which are demonstrated to improve diagnostic accuracy and image quality while reducing both radiation and contrast media administration. This review will summarize the technical basis of DECT and review the principal cardiac applications currently adopted in clinical practice, exploring possible future applications.